Modeling sea currents in working environment area of Parit Rempak Karimun port - Eny Budi Sri Haryani; Syofyan Hasan; Andika Bayu Candra (Depik, 2024)
Sea currents is an important indicator, especially if permanent infrastructure to be built in waters area. Based on Government Regulation No. 21/2O21 Regarding the Implementation of Spatial Planning, it is mandatory to have licensing for Sustainability of Marine Spatial Utilization Activities (SMSUA). Therefore, Karya Karimun Mandiri Company collaborated with authors to conduct this research at Parit Rempak port. This research only focus to sea current and aims to determine the existing conditions of sea currents and their modeling in planned location for construction of LPG-GFS jetty pier. The analysis includes surface current conditions, sea currents based on NOAA data, sea current rose directions, sea current modeling, bathymetry maps and sediment condition, which use primary and secondary data. Primary data was measured at 6 research stations, which were then analyzed using Mike 21 software. The research results showed that: (a) existing conditions surface current speed at high tide ranges from 0.0 to 0.83 m/s towards the east, at low tide it ranges from between 0.07 to 0.64 m/s towards the west; (b) based on NOAA data, sea currents at research location move relatively regularly and in a direction towards southeast, which were speed of sea currents varies according to season, with a range of 0.0 m/s to 0.125 m/s, non-tidal so it is relatively not turbulent; (c) sea current modeling that maximum current speed is 0.25 m/s and minimum current speed occurs at highest tides and lowest low tides, with direction of current movement to southwest and northeast; (d) bathymetric conditions with a depth between 0-5 meters, constitute shallow water and sediment consist of mud, muddy sand and gravelly sand, are safe for building a LPG-GFS jetty pier. Based on the conditions of sea currents and data above, SMSUA permits is eligible to be granted and must be issued.KeywordsSea currentHydro-oceanographicJetty pierCoastal ecosystemMarine spatial planningPort of Parit Rempak